STUDI PERENCANAAN PONDASI BORE PILE PADA PEMBANGUNAN GEDUNG TERMINAL BANDAR UDARA NGLORAM BLORA - Fatika Putri Setianingsih; Bambang Wasito; Karina Meilawati Eka Putri (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
One of the important parts in a building planning is foundation planning. The foundation is the lower structure of the building construction that is directly related to the ground and functions as a load-bearing building from above and will channel it into the ground. The existence of the foundation is not something that is not important, but has a big influence in the construction of the building to be built. The bore pile foundation is the foundation chosen for the Ngloram Airport construction project because it has several advantages such as the diameter and depth of the pile that can be changed as specified. The airport, which is located in the middle of the rice fields, has a type of clay soil, therefore the calculation of the magnitude of the load and the carrying capacity of the soil is very necessary in planning the foundation. The calculation of the carrying capacity is based on CPT data (cone penetration test) using 2 methods, namely Reese & Wright and O'neil & Reese. From the results of the analysis using the Reese & Wright method, Qijin was obtained at 483.1471 kN, while the results from O'neil & Reese obtained Qijin at 418.9704 kN. For the results of the calculation of the load calculated using the SAP 2000 application is 402.851 kN. So it can be concluded that the foundation is safe in holding the load on it.